When Is the Teacher? Reflections on Life Writing, Social Fiction, and Film - McKerracher, Adrian; Sinner, Anita; Hasebe-Ludt, Erika; Leggo, Carl; Rak, Shauna; Ahn, Claire; Boschee, Jana (La Revue de l’association canadienne pour l’étude de curriculum, 2016)
In this paper, seven Canadian curriculum researchers investigate and discuss life writing as a mode of educational inquiry and curricular theorizing through which educators can attend to the tensions and complexities of teaching and learning in a variety of curricular and pedagogical contexts. Drawing from their individual and collective research in creative methods of arts-based inquiry, they explore how life writing, with its multiple modalities between creative nonfiction, fiction, poetry, theatre arts, fine arts, and multimedia, can open up possibilities for researchers, teachers, and students to rethink and re-enact education as an inspiriting, heart-full, and empathetic endeavour.